Disordered haematopoiesis and athero-thrombosis - Murphy, Andrew J. (Eur Heart J, 2016)
Atherosclerosis, the major underlying cause of cardiovascular disease, is characterized by a lipid-driven infiltration of inflammatory cells in large and medium arteries. Increased production and activation of monocytes, neutrophils, and platelets, driven by hypercholesterolaemia and defective high-density lipoproteins-mediated cholesterol efflux, tissue necrosis and cytokine production after myocardial infarction, or metabolic abnormalities associated with diabetes, contribute to atherogenesis and athero-thrombosis. This suggests that in addition to traditional approaches of low-density lipoproteins lowering and anti-platelet drugs, therapies directed at abnormal haematopoiesis, including anti-inflammatory agents, drugs that suppress myelopoiesis, and excessive platelet production, rHDL infusions and anti-obesity and anti-diabetic agents, may help to prevent athero-thrombosis.